Key to the fossil genus Largusoperla (Plecoptera: Perlidae), with description of two new species from mid-Cretaceous Burmese amber - Chen, Zhi-Teng (Zootaxa, 2018)
Two new species of the fossil stonefly genus Largusoperla (Plecoptera: Perlidae), Largusoperla dewalti sp. nov. and Largusoperla borisi sp. nov. are described and illustrated from mid-Cretaceous Burmese amber. The two new species are distinguished from other known congeners by the specifically modified paraprocts. In addition, an identification key to the known species of Largusoperla is provided.